The Urge of Parents' Role: The Contributions of Parent and Peer Attachment to Adolescent’s Problematic Internet Use (PIU) - Mukti R, Yuliana; Bustan, Radhiya (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Indonesian adolescents spend too many hours using the internet. It leads to negative impacts, including problematic internet use (PIU). Few studies have found that social factors from parents and peers contribute to how they use the internet. Regardless, they still found inconsistencies regarding whether parents or peers, if investigated together, had the highest impact on their maladaptive internet use. This study aimed to examine the contribution of adolescent attachment to parents and peers to adolescents’ maladaptive internet use in terms of PIU. This research is using accidental sampling. The subjects were 237 adolescents (91 male) aged 12-24 years (M=15.03) from the Jabodetabek area. Data was collected using Google Forms. The PIU was measured using IPIUS (Indonesia Problematic Internet Use), and adolescents’ attachment was measured using IPPA (Inventory of Parent and Peer Attachment). Multiple regression with the stepwise model is applied to investigate the contribution of attachment to PIU. This paper argues that parent and peer attachment contributes significantly to adolescents’ PIU, and this parent attachment has a higher influence than peer attachment. This implies that optimizing parents’ role in attachment behavior could still impact adolescents’ internet behavior.